(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Recent concerns regarding global warming have resulted in an increasing need to decarbonize the world's energy sector, and consequently, sustainable energy development projects have been tremendously boosted in recent years. Due to the need to reduce carbon emissions and the need to use clean energy, electric vehicles (EVs) have skyrocketed as an alternative means of transportation due to the need for clean energy. This has resulted in rapid and multifaceted changes to the transport system that have affected a wide range of sectors. Even so, there has been a great deal of emphasis on research and development of EVs, with not enough attention paid to efficiency improvements and alternatives to using new technologies, which may further boost the advantages of EVs in the future. Aiming to increase real-time operation of EV systems with IoT to allow for scalable performance, increase autonomy, and improve performance in an ever-increasing market for electric vehicles, this paper addresses how the Internet of Things can be incorporated into EV systems using IoT in order to increase real-time operation. This paper reviews how these systems interact, as well as possible challenges and threats associated with incorporating IoT into EV systems, so that a way forward can be found in the quest for incorporating IoT into EV systems.